PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDIDIKAN KARAKTER PADA MATERI PECAHAN DI KELAS V MIN 2 PONTIANAK BARAT - Deti Seniati; Yulis Jamiah; Dede Suratman (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to develop a Student Worksheet (LKPD) based on character education on fractional material. This type of research is the Research and Development (R&D) method. The research and development design in this R&D uses the 4-D development model developed by Thiagarajan. Quantitative research data in this study were obtained from product assessments by validation experts and also the results of filling out questionnaires for teacher and student respondents. Quantitative data obtained from suggestions and notes by validators, teachers and students. The instruments in this research are questionnaire, interview and posttest guidelines. The level of validity of student worksheets is based on assessments from material experts, media experts, and language experts. As well as the level of practicality of the product based on the results of teacher and student assessments and learning outcomes based on the results of student tests. Based on the assessment by teachers and students of class V Madrasah Ibtidaiyah 2 West Pontiank. The validation results obtained an average percentage of 80.09% with valid criteria. The level of practicality of the Student Worksheet (LKPD) Based on Character Education in Pontianak fraction material obtained a percentage result of 82.51% with very practical criteria. Then the learning outcomes get 87.80% with very high criteria.